Regulation of transcription and chromatin structure by pRB: Here, there and everywhere - Talluri, Srikanth; Dick, Frederick A. (Cell cycle (Georgetown, Tex.), 2012)
Commitment to divide is one of the most crucial steps in the mammalian cell division cycle. It is critical for tissue and organismal homeostasis, and consequently is highly regulated. The vast majority of cancers evade proliferative control, further emphasizing the importance of the commitment step in cell cycle regulation. The Retinoblastoma (RB) tumor suppressor pathway regulates this decision-making step. Since being the subject of Knudson's 'two hit hypothesis', there has been considerable interest in understanding pRB's role in cancer. It is best known for repressing E2F dependent transcription of cell cycle genes. However, pRB's role in controlling chromatin structure is expanding and bringing it into new regulatory paradigms. In this review we discuss pRB function through protein-protein interactions, at the level of transcriptional regulation of individual promoters and in organizing higher order chromatin domains.